Do generational diversity and perceived similarity improve team functioning in rural Chinese hospitals? A cross-sectional survey study - Martina Buljac-Samardžić; Joris van de Klundert; Jeroen van Wijngaarden; Hujie Wang (BMJ Open)
Objectives Generational diversity, increasingly prominent in the composition of the healthcare workforce in rapidly developing countries, has received much attention in practice and research recently. While research has revealed various positive and negative impacts of generational diversity on team functioning, the understanding of the mechanism explaining how generational diversity influences team functioning is still limited. This study in rural Chinese hospitals examines the relationship between (surface-level) generational diversity and (deep-level) perceived similarity and investigates how they influence three teamwork behaviours that importantly determine quality of care, namely speaking up, silence and knowledge sharing.Design We adopted a quantitative research design and conducted an online survey to investigate the relationship among generational diversity, perceived similarity, speaking up, silence and knowledge sharing. Multilevel mediation modelling was used to test the hypotheses.Setting The study was conducted in four rural Chinese hospitals.Participants 841 healthcare professionals, including doctors, nurses and other healthcare professionals, were included in the study.Primary and secondary outcome measures Generational diversity was measured by calculating the average of individuals’ Blau’s indices regarding all the generations for each team. Perceived similarity, speaking up, silence and knowledge sharing were measured by validated questionnaires from literature.Results Perceived similarity is positively related to the three teamwork behaviours, that is, speaking up (β=0.56, p<0.01), silence (β=0.39, p<0.01) and knowledge sharing (β=0.54, p<0.01), while generational diversity is not (speaking up: β=0.08, p>0.05; silence: β=0.44, p>0.05; knowledge sharing: β=0.09, p>0.05). As the relationship between generational diversity and perceived similarity is non-significant (β=0.07, p>0.05), perceived similarity does not mediate the relationship between generational diversity and teamwork behaviour.Conclusion The findings suggest that increases in generational diversity that result from healthcare workforce strengthening may not impact team behaviours and performance. However, if healthcare workforce strengthening would reduce the perceived similarity in teams, explicit management efforts to mitigate the negative impact on team behaviour and care provision are called for.